Ninguém pode servir a dois senhores (Mt 6,24): a relação entre governamentalidade neoliberal e idolatria na perspectiva do Reinado de Deus - Morais, Julio Cezar Nascimento (2024)
The object of study of this dissertation is the relationship between theology and economics. It seeks to develop a theological critique of neoliberalism, characterizing it as true idolatry, based on the notion of the Reign of God. The aim is to demonstrate the pertinence and relevance of the presentation of Christian salvation, summarized in the category “Kingdom of God”, as a way of guiding human beings towards an authentically human life, totally opposed to neoliberal governmentality, which is thus configured as idolatry. In this “God x idol” opposition, we see the opposition between two projects for guiding human beings: one that really wants to lead to life, and another that, despite presenting itself as a director of happiness and human life, in fact, leads to death. Our hypothesis is that, by presenting the God’s project for humanity in these terms and denouncing neoliberalism as a project that rivals God's, therefore, as idolatry; thus, the themes of the Christian faith gain greater concreteness and credibility among men and women of nowadays. This idea would make possible to show that what christian faith deals with is something serious and concerns everyone, because it deals with concrete human life, a life that is threatened by the neoliberal idolatry of the market. In this research, a descriptive-analytical approach to the object of study is adopted, from a phenomenological perspective, based on the critical assessment of sources and authors that help to support our argument in the intended direction. The work is divided into three chapters. In the first one, there is a brief historical review of the origins and consolidation process of neoliberalism as a hegemonic form of government, whose reference point is the 1980’s. It analyzes what neoliberalism is and how it works, in addition to present some brief approximations between the themes of neoliberalism and of idolatry. In the second one, there is the development of central themes and concepts to this research intent. We seek to establish here the meaning of the theological perspective in the analysis of reality, in order to understand how, in the constitution of reality, elements of a theological nature operate and give rise to idolatrous conceptions of economic processes. The concept of idolatry is also presented and deepened, highlighting that it is characterized by a double aspect: an absolutizing and a sacrificial. From there, we begin to establish the criteria for discerning the “gods who are fighting” for the human heart. Finally, in the third and final chapter, an effort is made to present the salvation that configures the Christian proposal, summarized in the symbol of the “Reign of God”, as a not only reasonable, but authentic path to humanization and a path to overcoming the serious crises that humanity has been going through. The Kingdom of God, as Jesus reveals it, appears as a true “counter-conduct”, or “spirituality”, in the Foucauldian sense, which generates a new individual, who lives under the logic of love, thus founding a new order of things, established on new relationships characterized by fraternity and solidarity